PENGARUH PEMAHAMAN PERATURAN, OMSET, SANKSI, DAN RELASI SOSIAL TERHADAP KEPATUHAN WAJIB PAJAK (Studi Kasus Wajib Pajak Restoran Kota Pekanbaru Tahun 2012-2016) - Indah Dwiastari; Zirman Zirman; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to find out the effect of understanding the rule, turnover, sanctions, and social relations against tax compliance. In this research used the population that obtained by researchers amounted to 2.489 population and the sample was 96 respondents. The sampling technique in this research is proportionate stratified random sampling and obtain 44 restaurants, 31 café/coffee shop, 20 canteens. The technique of collecting data used was primary data obtained from questionnaires. Data analysis conducted with multiple regression model with help of software SPSS version 21,0. The variables used in this study are understanding the rules, turnover, sanctions, social relations and tax compliance. The calculation of dependent and independent variables using indicators from previous research questionnaire. Of the result of the testing that has been done, that understanding the rule, sanctions, and social relations has significant value on tax compliance. Meanwhile turnover have no significant effect on tax compliance. The results from coefficient determination (adjusted R2) test is worth 0.512. The conclusion from overall effect of independent variables is 51.2% while the remaining 48,8% is influenced by other independent variables that were not examined and used in this study.Keywords: Understanding The Rules, Turnover, Sanctions, Social Relations and Tax Compliance.